Growth is good for the poor - Dollar, David, 1954- 1954- (Policy research working paper, 2001)
When average incomes rise, the average incomes of the poorest fifth of society rise proportionately. This holds across regions, periods, income levels, and growth rates. But relatively little is known about the broad forces that account for the variations across countries and across time in the share of income accruing to the poorest fifth